Inhibition of MERS-CoV papain-like protease by sunitinib: In vitro and in silico investigations - Ahmed L. Alaofi; Mudassar Shahid; Mohd Abul Kalam (Pharmacia)
Middle East Respiratory Syndrome Coronavirus (MERS-CoV) remains a significant public health threat, with high mortality rates and no approved antiviral therapies. The papain-like protease (PLpro) of MERS-CoV plays a critical role in viral replication and immune evasion, making it a key target for drug discovery. This study evaluated the inhibitory effects of four anticancer drugs (sunitinib, olaparib, mitoxantrone, and bicalutamide) on recombinant MERS-CoV PLpro using a combination of in vitro and in silico techniques. Protease inhibition assays revealed that sunitinib displayed potent, dose-dependent inhibition of PLpro activity, with an IC50 of 1.75 µM, while olaparib, mitoxantrone, and bicalutamide exhibited negligible inhibition. Thermal shift assays confirmed the strong interaction of sunitinib with PLpro, showing a ΔTm of 26.64 °C, indicative of increased protein stability. Furthermore, molecular dynamics (MD) simulations and docking studies provided structural insights into the mechanism of inhibition. Sunitinib bound within the thumb domain of PLpro, forming stable interactions with residues such as D76, R82, and F79. Binding induced significant stabilization of PLpro’s structure, reducing flexibility in critical regions, including the thumb and catalytic domains, as indicated by a decreased radius of gyration and alterations in the free energy landscape. Importantly, the stabilization of PLpro by sunitinib was consistent between in vitro and in silico analyses, highlighting its robust inhibitory potential. These findings position sunitinib as a promising inhibitor of MERS-CoV PLpro, with strong binding affinity and the ability to disrupt enzymatic function. Further preclinical studies are warranted to explore its therapeutic potential against MERS-CoV. This study underscores the utility of repurposing existing drugs for emerging viral threats and contributes to the development of targeted antiviral strategies.